LEADING CHANGE: ROLE OF THE LEADER IN CHANGE PROCESS - Suryani, Meilati; Aliarosa, Windasari (Jurnal Kesehatan Budi Luhur : Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2022)
Change is an ongoing commitment that involves diffusion of the idea. Change is always occurring within health care, whether it is the update of a hospital policy or the implementation of an evidence base practice technique. Nurse leaders need to act as agent of change, to implement changes that will benefit nursing practice and improve quality of patient care. Kurt Lewin developed a change model involving three steps: unfreezing, changing and refreezing. Another approach that can be done is to adopt the ADKAR model. The ADKAR model outlines five milestones that an individual, unit, or group must achieve to change successfully: Awareness, Desire, Knowledge, Ability and Reinforce. Keywords : Change, ADKAR Model, Change Process